INFLUENCE OF THE TEMPERATURE COMBUSTION OF FUEL-WOOD TO CONTENT ASH - Dzurenda, Ladislav; Banski, Adrián (Innovation in Woodworking Industry and Engineering design, 2017)
In this contribution, there are presented the results of experiments determining the influence of combustion temperature of fuel-wood on the production of ash. They confirm current knowledge about the low production of ash from wood, and specify the functional dependences between the influence of temperature at intervals of t = 500°C – 1000 °C on the production of ash from the wood of tree species: Norway spruce, White birch, European beech, English oak and Black locust. The functional dependences of ash production on the combustion temperatures are instrumental for objectification of information about ash production from energy facilitiesfor energy, environmental, and ecological analyses and balances. The proportion of ash from fuel-wood can be done according to standard ISO 1171:2003, or standard EN14775:2010. These standards differ in the temperature of combustion of the fuel wood sample. ISO 1171:2003 burns fuel at t = 815 °C while EN14775:2010 at t = 550 °C. Disregarding the aforementioned facts about the dependence of production of ash on the combustion temperature causes errors. By interchanging the norms ISO1171:2003 with EN14775:2010, the balances from combustion of spruce wood generate a relative error of 44.58%. The balances from combustion of wood of black locust generate a relative error of 19.10%.